2014
DOI: 10.1063/1.4894617
|View full text |Cite
|
Sign up to set email alerts
|

A combined kick-out and dissociative diffusion mechanism of grown-in Be in InGaAs and InGaAsP. A new finite difference-Bairstow method for solution of the diffusion equations

Abstract: Experimental results on the diffusion of grown-in beryllium (Be) in indium gallium arsenide (In0.53Ga0.47As) and indium gallium arsenide phosphide (In0.73Ga0.27As0.58P0.42) gas source molecular beam epitaxy alloys lattice-matched to indium phosphide (InP) can be successfully explained in terms of a combined kick-out and dissociative diffusion mechanism, involving neutral Be interstitials (Bei0), singly positively charged gallium (Ga), indium (In) self-interstitials (IIII+) and singly positively charged Ga, In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…For example, in previous continuum or Monte Carlo studies, parameters entering the model such as charge states and reaction energies / diffusion barriers for elementary reactionson which the diffusion rate critically depends -were postulated or fitted rather than derived from first principles. 5,6 The experiments on Be diffusion are still relatively limited, which means that by tuning parameters and postulating different diffusion mechanisms one can achieve a good fit to diffusion profiles obtained in specific experimental conditions 3,4,7 , however, such fitting is not very meaningful because of the number of approximation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in previous continuum or Monte Carlo studies, parameters entering the model such as charge states and reaction energies / diffusion barriers for elementary reactionson which the diffusion rate critically depends -were postulated or fitted rather than derived from first principles. 5,6 The experiments on Be diffusion are still relatively limited, which means that by tuning parameters and postulating different diffusion mechanisms one can achieve a good fit to diffusion profiles obtained in specific experimental conditions 3,4,7 , however, such fitting is not very meaningful because of the number of approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the following, we consider only experiments where the only difference in conditions are annealing temperatures and durations. 2,6,10,16 Specifically, we consider experiments where: (i) the doping process is done by gas source molecular beam epitaxy rather than ion implantation or in-diffusion from an extended source, both of which will induce implantation damage or surface effect, which are difficult to account for in a simulation; (ii) the gas source molecular beam epitaxy parameters are similar. It is well known that such parameters will strongly influence the material's transport properties.…”
Section: Continuum Calculationsmentioning
confidence: 99%
“…Some modified models have been proposed in order to overcome the above limitations. 6 Recently, Koumetz et al proposed a combined diffusion mechanism, which removes the local thermodynamic equilibrium assumption and also takes the Frank-Turnbull (dissociative) mechanism (Be i + V III − − Be III ) into account, in which V III represents Ga and In vacancies, to explain the experimental data. Their simulation results suggested that the temperature dependence of group-III self-interstitial and of group-III vacancy effective diffusion coefficients are different.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations